Exploring Core Principles of Machine Learning for Advancing Intelligent Computing Paradigms - Rizky A, Galih Prakoso (Cebong Journal, 2025)
This research explores the core principles of machine learning (ML) as the foundation for advancing intelligent computing paradigms. As data-driven technologies rapidly evolve, ML has emerged as a central component in enabling adaptive, autonomous, and context-aware systems across various domains, from healthcare and finance to smart cities and industrial automation. Through a comprehensive review and analysis, the study examines fundamental ML techniques including supervised, unsupervised, reinforcement, and deep learning and evaluates their role in shaping computational intelligence. The methodology integrates conceptual analysis, synthesis of existing literature, and comparative evaluation of paradigms to highlight how ML differentiates itself from traditional algorithmic approaches. Findings reveal that ML not only enhances predictive accuracy and decision-making but also introduces new paradigms of adaptability, scalability, and self-learning, which are crucial for future intelligent systems. However, challenges such as data quality, interpretability, ethical concerns, and computational resource demands present limitations that must be addressed to ensure sustainable and responsible integration. This research contributes theoretically by refining the understanding of ML’s role in computational intelligence, practically by outlining its applications in real-world intelligent systems, and futuristically by framing new paradigms that combine technical advancement with ethical and policy considerations.